Data for: A model to examine farm household trade-offs and synergies with an application to smallholders in Vietnam - Groot, Jeroen C.J.; Timler, Carl J.; Chiang, Tsai-Wei; Abe Chatterjee, Shantonu; Komarek, Adam M.; Estrada-Carmona, Natalia; Kennedy, Gina; Álvarez, Stéphanie; Raneri, Jessica Evelyn; Ditzler, Lenora (2019)
FarmDESIGN Model with the case study farms and their data for the paper "A model to examine farm household trade-offs and synergies with an application to smallholders in Vietnam"